Empreendedorismo ambiental e preservacionismo compensatório: o turismo e as unidades de conservação Parque Estadual das Dunas e Área de Proteção Ambiental Jenipabu-RN - Fernandes, Maria Célia (2011)
This doctoral thesis addresses the environmental issues and its vinculum with the tourism through the protected natural areas, in particular the conservation units, which consists in territorial areas created and demarcated by the government in order to protect ecosystems that have a high ecological and scenic-landscaped representativeness designed to the contemplation and controlled public visitation. In regard to its use for the touristic activities, are conceived while socio-environmental and symbolic materiality built around an imagery view of a nature-show, designed to attract visitors, aiming ensure the maintenance and reproduction of the capital in an entrepreneurial and preservationist way in the Metropolitan Region of Natal. It s a study about the Dunes State Park Jornalista José Maria Alves and the Jenipabu Environmental Protected Area, both created with the purpose of favor the implantation and empowerment of the touristic area through the State intervention as the main articulator agent of a new process of urbanization that uses the city marketing and the ideological discuss of environmental sustainability to recreate the imaginary of lost paradise and incorporate into the daily universe of tourists visiting the state of Rio Grande do Norte. The unveiling of this empirical reality made possible the construction and defense of the terms environmental entrepreneurship and compensatory preservationism, to explain how the formatting and idealization of this paradisiacal scenarios produce the commoditization of nature in an efficient and competitive way